Influence of steric factors on reversible reactions of hydrogenation-dehydrogenation of polycyclic aromatic hydrocarbons on a Pt/C catalyst in hydrogen storage systems. (15th November 2020) - Kalenchuk, Alexander; Bogdan, Viktor; Dunaev, Sergei; Kustov, Leonid
Graphical abstract: Highlights: Reversible hydrogenation-dehydrogenation of polycyclic hydrocarbons was studied. Activation energies and pre-exponents of both processes were determined. Correlations of reaction rates with the structure and condensation extent were found. Abstract: The reversible reactions of hydrogenation-dehydrogenation of polycyclic aromatic hydrocarbons with a different extent of condensation (naphthalene, anthracene, biphenyl, meta- and para -terphenyl isomers) were studied in comparison with benzene on a 3%Pt/C catalyst. Hydrogenation of naphthalene and anthracene was carried out at T  = 280 °C, P  = 90 atm, whereas the reaction of benzene, biphenyl and terphenyl isomers was performed at T  = 180 °C, P  = 70 atm in an autoclave. Dehydrogenation of the corresponding polycyclic naphthenes (cyclohexane, decalin, perhydroanthracene, bicyclohexyl, ortho, meta, and para -isomers of perhydroterphenyl) was carried out in the temperature range of 280 to 340 °C in a flow setup at the volume hourly space velocity of 1 h −1 and atmospheric pressure. Correlation dependences of the reaction rates of hydrogenation-dehydrogenation of the studied substrates on their structure and extent of condensation were found.